Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1788 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Panicum parvifolium Lam.", "BasisOfRecord is Specimen" ] } The dataset includes 1788 records from 83 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003676-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences